Variability and character association in paprika and paprika alike chillies - N K Leela, T John Zachariah, K N Shiva, D Prasath, P Gobinath, (Journal of Spices and Aromatic Crops, 2017)
An experiment was conducted to estimate variability and character association in a set of 25 indigenous (paprika alike chillies) and 18 exotic (paprika) germplasm of paprika. Wide range of variation was observed for all the characters except for capsaicin content, weight of seeds, fruit girth and length. The maximum range of variation was recorded for yield plant-1 followed by color value, plant height and number of seeds fruit-1. Among the various traits, maximum coefficient of variation was observed for capsaicin content, followed by weight of pericarp fruit-1, yield plant-1 and weight of seeds fruit-1 in the indigenous lines of paprika. Similarly, in the exotic and combined germplasm of paprika and paprika alike chillies, maximum range of variation was registered with yield plant-1, followed by color value, number of seeds fruit-1 and plant height and narrow range of variation was observed with capsaicin content. In the combined germplasm, maximum coefficient of variation was recorded with capsaicin content, followed by weight of pericarp fruit-1, yield plant-1 and color value. Weight of pericarp, number and weight of seeds fruit-1 were identified as important yield components and selection should be focused on these traits for improvement of paprika and paprika alike chillies.